Distress symptoms in older adults: results from the Survey for Health and Retirement in Europe. (20th October 2021) - Shahaj, O; Ksinan, A; Bobak, M; Pikhart, H
Abstract:  : The enforced isolation that followed the first wave of SARS-CoV-2 outbreaks led to widespread concern regarding its unintended consequences on the mental well-being of older adults. The onset and severity of the outbreak, as well as the restrictive measures varied widely across countries. We aim to identify both individual and contextual factors that may have affected the presence and worsening of distress symptoms among older adults in 27 European countries. 52, 310 non-institutionalised participants were asked about feeling depressed, anxious, lonely, and having trouble sleeping in the 4 weeks preceding the interview. The answers were combined into a count variable measuring distress. Answers regarding worsening of these symptoms during the outbreak were treated as binary variables. Multilevel zero-inflated negative binomial and binary logistic regressions were used to analyse the outcomes. Increasing age is not associated with higher rates of distress (p = 0.12) and compared to those aged <60, those aged 71-80 and 80+ are 33% and 46% less likely to report feeling more depressed than before the pandemic (p < 0.001). Female gender, living alone, poor physical health, low education and reduced social contact were all linked to higher rates of distress (p < 0.001). Living in a country with stronger restrictions is linked to higher distress p < 0.031 while higher Covid-19 deaths/million are associated with worsening of all four symptoms [OR: depressed 1.14(1.01-1.29); nervous 1.15(1.03-1.28); sleep troubles 1.19(1.08-1.32) and loneliness 1.14 (1.02 - 1.28)] Individual factors associated with the presence and worsening of depressive symptoms during the pandemic are similar to the ones reported in the literature before the pandemic. These groups may require additional support and mental health services. The stringency of restrictions and Covid-19 death toll adversely affected mental health, but older adults seem to be more resilient than their younger peers. Key messages: The negative impact of the outbreak has been stronger on socially disadvantaged older adults. Strong restrictions to contain the outbreaks may lead to increase in distress symptoms in older adults but older adults are more resilient than their younger peers.